ANALYSIS OF FOOD AND AGRICULTURE ORGANIZATION (FAO)'S ROLE IN REALIZING SDG'S "ZERO HUNGER" IN CONFLICT COUNTRIES CASE STUDY: YEMEN - ZAHRA AMALIA; AURELIA PUTRI NOVERI; IDA SUSILOWATI (MANU Journal of Humanities, 2023)
The writing of this article aims to analyze the role of Food and Agriculture Organization (FAO) in responding to the food crisis in Yemen as a Sustainable Development Goals (SDG)'s goal. This research uses a systematic review with qualitative research methods sourced from previous research such as journals, websites, and books to analyze more deeply the role of FAO on the issue of food security in Yemen. This is evidenced by the food crisis in Yemen in 2008 due to the increase in global food prices and 2011 Yemen was hit by a known issue of civil unrest as the Arab Spring which makes the security situation continue to deteriorate. As the FAO proves Yemen is facing the world's largest food security crisis. The agricultural sector is one of the sectors most affected by this crisis. The FAO has an action plan in response to the Yemeni crisis. The purpose of this study is to determine the role of FAO in realizing SDG's "zero hunger" in Yemen, which is a conflict country. The study found that FAO collaborates with International Organizations comprehensively focused on recovery and development. This shows that FAO has an important role in realizing SDG's "zero hunger" against the food crisis in Yemen.